Market Penetration Traffic Referencing Seasonal Patterns based on Marketing Value - Andriyansah, Andriyansah; Puji, Sri Lestari; Maesaroh, Imas; Ayuni, Devi; Minrohayati, Minrohayati; Firmansyah, Firmansyah; Yolanda, Ledy (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study analyses market penetration traffic as a strategic instrument integrating value-based marketing with market performance. Using a descriptive qualitative approach, this study identifies three zones of market penetration traffic: green, yellow, and red. The findings show that the effectiveness of market penetration depends on the company's ability to integrate value-based marketing with market sensing capability. The green zone requires maintenance and expansion strategies, the yellow zone needs strategy optimisation, and the red zone necessitates fundamental transformation. The findings indicate the importance of continuously monitoring traffic indicators for marketing strategy adjustment. Managerial implications emphasise the development of effective feedback mechanisms to optimise market penetration and customer value creation.